PENDIDIKAN KEAGAMAAN DAN MASYARAKAT MINORITAS (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractThe research undertaken in one of regencies with Moslem minority is aimed at understanding the condition of religious educational institutions, religious values taught and community expectation with respect to religious education in the future. The research findings show that numerous components of religious educational institutions, including their numbers, were so insufficient. The types of religious educations provided were oriented to the cultivation of religious principles such as faith-morals, daily prayers, and al-Quran reading and writing. Community expected that religious education in the future be increased both in their quantity and the quality of the materials transferred.